(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Background: Dermtoglyphics are the lines and ridges forming a skin pattern, especially on the palm of the hands, fingertips and soles of feet. Differentiations of dermal ridges in early life are genetically determined1. Any disturbance by genetic factors causes development of unusual dermatoglyphics. On the other hand, deficiency of Mannose binding protein (MBP) gene and Interleukin-1 (IL-1) gene cause spread of pulmonary tuberculosis2. The dermatoglyphic pattern in patient with pulmonary tuberculosis can represent an anatomical, non-invasive, inexpensive tool for screening high-risk population, and facilitates early prediction of vulnerable population of PTB. Materials and Methods: A Cross-sectional, analytical type of study was conducted in Department of Anatomy, Dhaka Medical College, Dhaka, from January 2012 to December 2012. The study was performed in 100 patients suffering from pulmonary tuberculosis and 100 healthy individuals. Results: There was significant reduction in mean±SD of atd angle in pulmonary tuberculosis patients in comparison to control subjects. Mean±SD of atd angle was 37.87±3.403 in pulmonary tuberculosis patients and 49.77±4.628 in the control subjects. The difference was highly significant (P<0.001). Conclusion: The atd angle was found significantly narrower in the study group compared to the control subjects. Anwer Khan Modern Medical College Journal Vol. 8, No. 2: Jul 2017, P 85-88